THE EFFECTIVENESS OF VISUAL ILLUSTRATIONS IN INCREASING STUDENTS’ READING COMPREHENSION SKILLS IN TENTH GRADE AT SMK NU PACE - Nurul Yulaekah; Anita Budi Rahayu (Universitas PGRI Mpu Sindok, 2025)
Visual illustrations represent text or ideas with real and authentic contexts, which can improve students' reading comprehension and attract their interest in learning. The purpose of this study is to analyze significant differences in students' reading comprehension skills before and after being taught using visual illustrations. This study used quantitative method and quasi-experimental design of one group pre-test and post-test. The sample technique used was convenience sampling. Data collection techniques were pre-test and post-test with 10 multiple choice questions. Data analysis techniques using descriptive statistics and inferential statistics. The results showed that the average pre-test score was 58.1 in the low category and the average post-test was 82.6 in the very good category. Based on the results of the t-test analysis obtained tcount (1.96) > ttable (1683). So, Ha is accepted and H0 is rejected. The n-gain score of 0.58 (58%) shows the effectiveness of visual illustration in improving students' reading comprehension. Thus, there is a significant difference in student learning outcomes through the use of visual illustration in increasing students’ reading comprehension skills in tenth grade at SMK NU Pace in the academic year of 2023/2024.